2020
DOI: 10.1038/s41598-020-60578-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Proteins in Human Skeletal Muscle: The Role of Transcription

Abstract: Regular low intensity aerobic exercise (aerobic training) provides effective protection against various metabolic disorders. Here, the roles played by transient transcriptome responses to acute exercise and by changes in baseline gene expression during up-regulation of protein content in human skeletalmuscle were investigated after 2 months of aerobic training. Seven untrained males were involved in a 2 month aerobic cycling training program. Mass-spectrometry and RNA sequencing were used to evaluate proteome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…Notably, a previous study found that the same number of genes encoding mitochondrial proteins were expressed at lower levels in sarcopenic human VL muscle showing low mitochondrial density than in age-matched controls [ 70 ]. In agreement with our previous findings [ 20 , 35 ], our current analysis revealed that acute and regular exercise induced the expression of only a few genes (2% and 3%) encoding mitochondrial proteins ( Figure 3 a, Table 2 and Table S4 ). It is possible that acute exercise-induced up-regulation of these genes may occur in the latter stages of recovery.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Notably, a previous study found that the same number of genes encoding mitochondrial proteins were expressed at lower levels in sarcopenic human VL muscle showing low mitochondrial density than in age-matched controls [ 70 ]. In agreement with our previous findings [ 20 , 35 ], our current analysis revealed that acute and regular exercise induced the expression of only a few genes (2% and 3%) encoding mitochondrial proteins ( Figure 3 a, Table 2 and Table S4 ). It is possible that acute exercise-induced up-regulation of these genes may occur in the latter stages of recovery.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we found that regular aerobic exercise substantially up-regulated more than a half of genes encoding muscle collagens, as well as a number of ECM glycoproteins and proteoglycans (47 genes in total: 56%, 25% and 32% of the corresponding genes, respectively), including the two most abundant muscle ECM proteins: collagen alpha-1 (I and III) accounting for more than half of the ECM proteins in skeletal muscle [ 60 ] ( Figure 3 b, Table 2 and Table S4 ). These responses were predominantly related to changes in the baseline gene expression induced by long-term training and support the notion that ECM proteins are closely regulated at a transcriptional level [ 35 ]. Only a few enzymatic ECM regulators are known to be involved in disuse- and training-induced ECM remodeling in skeletal muscle (reviewed in [ 46 , 47 ]).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In this respect, it has been shown that protein expression in skeletal muscle is weakly regulated at the mRNA level leading to big differences in mRNA and protein abundance in various tissues (Wang et al, 2019). Interestingly, the pattern of protein regulation depends on protein function, whereby the association between mRNA and protein is higher for ECM and collagen fibril organization (Makhnovskii et al, 2020). Another interesting aspect in the regulation of the amount of ECM proteins is the fact that induction of transcription seems to be rather slow for collagen as it takes almost 3 days to fully induce transcription.…”
Section: Physiological Regulation Of Ecm Genesmentioning
confidence: 99%